Presenting a New Framework to Improve Engagement in Physical Activity Programs for Children and Adolescents With Social, Emotional, and Behavioral Disabilities - Bowling, April B.; Frazier, Jean A.; Staiano, Amanda E.; Broder-Fingert, Sarabeth; Curtin, Carol (Frontiers in Psychiatry, 2022)
Children and adolescents with psychiatric and neurodevelopmental diagnoses such as anxiety, depression, autism, and attention-deficit/hyperactivity disorder (ADHD) face enormous health disparities, and the prevalence of these disorders is increasing. Social, emotional, and behavioral disabilities (SEBD) often co-occur with each other and are associated with unique barriers to engaging in free-living physical activity (PA), community-based exercise and sports programming, and school-based physical education. Some examples of these barriers include the significantly depleted parental reserve capacity associated with SEBD in children, child dysregulation, and previous negative experiences with PA programming and/or exclusion. Importantly, most SEBD are “invisible,” so these parents and children may face more stigma, have less support, and fewer inclusive programming opportunities than are typically available for children with physical or intellectual disabilities. Children’s challenging behavioral characteristics are not visibly attributable to a medical or physical condition, and thus are not often viewed empathetically, and cannot easily be managed in the context of programming. Existing research into PA engagement barriers and facilitators shows significant gaps in existing health behavior change (HBC) theories and implementation frameworks that result in a failure to address unique needs of youth with SEBD and their parents. Addressing these gaps necessitates the creation of a simple but comprehensive framework that can better guide the development and implementation of engaging, effective, and scalable PA programming for these youth and their families. Therefore, the aim of this article is to: (1) summarize existing research into SEBD-related child and parent-level barriers and facilitators of PA evidence-based program engagement; (2) review the application of the most commonly used HBC and disability health theories used in the development of evidence-based PA programs, and implementation science frameworks used in adaptation and dissemination efforts; (3) review the SEBD-related gaps that may negatively affect engagement; and (4) describe the new Pediatric Physical Activity Engagement for Invisible Social, Emotional, and Behavioral Disabilities (PAID) Framework, a comprehensive adapted PA intervention development and implementation adaptation framework that we created specifically for youth with SEBD and their parents.